Dietary simple sugar intake, metabolic indicators, markers of inflammation, and injury among semi-professional football players - Jun Hou; Yuemei Cui; Jun Gao; Ming Rong (Food & Nutrition Research)
Background: Dietary sugar intake has been implicated in the development of metabolic dysfunction, chronic inflammation, and immune dysfunction, contributing to the pathogenesis of various diseases. This study aimed to investigate the associations between dietary total simple sugar intake and glycemic markers, lipid profile, serum levels of high-sensitivity C-reactive protein (hs-CRP), and adenosine deaminase activity (ADA), among semi-professional football players. Methods: A cross-sectional study was conducted among 108 semi-professional football players. Dietary intake of simple sugars was assessed using validated dietary assessment tools, while serum levels of biochemical variables were measured using standard laboratory assays. Multinomial logistic regression analysis and partial correlation analysis were performed to examine the associations between dietary simple sugars and serum biomarkers, adjusting for confounders. Results: Strong positive associations were observed between dietary total simple sugar intake and hs-CRP and ADA levels in multinomial regression analysis. Also, among individual assessment of dietary simple sugars, dietary fructose and glucose intake were positively correlated with serum hs-CRP levels (r = 0.484, P < 0.001 and r = 0.393, P < 0.001, respectively) and serum ADA levels (r = 0.233, P = 0.001 for glucose; r = 0.188, P = 0.01 for fructose). There was no other association between dietary simple sugar intake and metabolic parameters. Conclusion: Our findings highlight the significant impact of dietary sugar intake on inflammation, as reflected by serum hs-CRP and ADA levels. Strategies aimed at reducing sugar consumption may help mitigate inflammation and improve overall health outcomes. Further research is warranted to elucidate the underlying mechanisms and to explore potential therapeutic interventions targeting dietary sugar intake for the prevention and management of chronic diseases.